Studying Visual and Spatial Reasoning for Design Creativity - Gero, John S (Springer, 2015)
Design has become a fruitful research area for cognitive scientists and computer scientists, not only for design scientists. For cognitive scientists it represents a par ticularly rich and open environment within which to study complex human behav ior. For computer scientists it represents a challenging area. For design scientists the tools to study and model designers are only now becoming available. For neurosci entists design is largely a novel domain...